Skew-symmetric tensor decomposition - Arrondo, Enrique (2021)
We introduce the "skew apolarity lemma" and we use it to give algorithms for the skew- symmetric rank and the decompositions of tensors in the dth exterior power of a vector space V, with d at most 3 and dim V at most 8. New algorithms to compute the rank and a minimal decomposition of a tritensor are also presented.